THE REPRESENTATION OF IRAN AND UNITED STATES IN DONALD TRUMP’S SPEECH: A CRITICAL DISCOURSE ANALYSIS - Paulina Sefrinta Indah Ivana; Suprayogi Suprayogi (Linguistics and Literature Students' Journal, 2020)
Speech plays an important role to shape public perception as it is delivered by an influential figure and reflects the points of view of its speaker. This study discusses a speech delivered by the United States President, Donald Trump, which discusses the conflict between Iran and America. This study was conducted to reveal the representation of Iran and the United States in one of Donald Trump’s speeches. The method used in this study is the descriptive qualitative method. The data in this study are in the form of words, phrases, clauses, and sentences that indicate the position of Iran and the United States taken from the speech transcript from the official website of The White House. Data were analyzed under the framework of Van Djik’s Socio-Cognitive Approach, consisting of text, socio-cognitive, and social context. Based on the analysis, it can be concluded that Iran is described as a country that has nuclear ambitions and acts of terror that support the existence of terrorists. On the other hand, America is described as having an invincible power. At a socio-cognitive level, Donald Trump is considered a knowledgeable figure on his country’s political condition because he knows the weaknesses of Iran and can properly take every decision. Donald Trump also has the authority as a President to make The United States and the countries of the world can work together for peace world. Thus, from the level of social context, countries in the world support the actions taken by America and are very alarming about what Iran has done. The finding suggests that the Socio-cognitive approach is practical to analyze the representation of an issue in speech reflected in linguistics expression and the discourse structure.